Mitochondrial polymorphism of sea beet (Beta vulgaris ssp. maritima), a species with cytoplasmic male sterility - Tomoki Murata; Hiroyo Kagami-Katsuyama; Mion Oishi; Haruto Tanaka; Chihiro Sano; Jun Kashikura; Ryo Hayakawa; Keishi Kubota; Eigo Taniguchi; Keita Suzuki; Kazuyoshi Kitazaki; Tomohiko Kubo (PLoS ONE, 2025)
Cytoplasmic male sterility (CMS), a form of mitochondrion-induced male sterility, is a valuable trait for hybrid breeding in crop production. However, CMS is not universally present across all crop species, prompting ongoing efforts to identify CMS sources within genetic resources. The discovery of CMS could be facilitated by the development of predictive indices indicating the presence of CMS-associated mitochondria. One theory has proposed that populations containing CMS-expressing plants exhibit elevated mitochondrial polymorphism. Sea beet, a species known to harbor CMS, provides a suitable system for testing this prediction. We first conducted network analysis by using mitochondrial single nucleotide polymorphism sites extracted from publicly available nucleotide sequence data. The resulting network, constructed from 270 sea beet sequences, was complex yet characterized by several star-like clusters. Haplotypes from Mediterranean region were dispersed across the network, while those from Atlantic coast tended to cluster, supporting the hypothesis that sea beet originated in the Mediterranean area and later migrated to the Atlantic coast. We then analyzed four mitochondrial minisatellites—variable number of tandem repeat loci— across 973 plants of 172 sea beet accessions. Combination of alleles at these four loci defined 29 distinct mitotypes. Analysis of mitotype distribution revealed similarly high mitochondrial polymorphism (~0.87) in both the Mediterranean and the Atlantic regions, despite their genic differentiation. Most subregions within these areas contained 8–15 mitotypes; however, Denmark was a notable exception, with only a single mitotype detected among 139 plants from 11 accessions. This mitochondrial monomorphism contrasts with the diversity observed in neighboring Atlantic subregions, indicating that Danish sea beet constitutes an exceptional population. Notably, the Danish mitotype was not associated with any CMS, suggesting that the population may be devoid of CMS mitochondria— a condition in which the proposed mechanism for increased mitochondrial polymorphism would not be operative.